Pengembangan Strategi Usaha Penyulingan Minyak Daun Cengkeh di Desa Sabang Kecamatan Dampelas Kabupaten Donggala - Abd.Majid, Muliana,Rukavina Baksh,Dance Tangkesalu, Ronald (AGROTEKBIS, 2015)
This Research aim is to determine the right strategy to develop clove leaf oil refining business in the Sabang Village Dampelas Subdistrict, Donggala Regency. This research was conducted in February until Maret 2015. Determination of respondent committed intentionally (purposive) and respondents choosen was 10 people. The SWOT analysis was used to analysis the data. The analytical results showel that the right strategy to development is SO Strengths (powers) -Opportunities (opportunities) strategy to use the force to take advantage of the opportunity to obtain two alternatives that is: maximizing the use of technology to access information on existing technologies to improve the quality of production company, promoting a quality product from the company to be more popular among consumers by utilizing information and communication technologies available.